Search for anomalous couplings in boosted W W / W Z → ℓ ν q q ‾ production in proton–proton collisions at s = 8 TeV - Sirunyan, A.M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; Frühwirth, R.; et al. (Elsevier, 2017)
This Letter presents a search for new physics manifested as anomalous triple gauge boson couplings in WW and WZ diboson production in proton–proton collisions. The search is performed using events containing a W boson that decays leptonically and a W or Z boson whose decay products are merged into a single reconstructed jet. The data, collected at s=8 TeV with the CMS detector at the LHC, correspond to an integrated luminosity of 19 fb−1. No evidence for anomalous triple gauge couplings is found and the following 95% confidence level limits are set on their values: λ ([−0.011,0.011]), Δκγ ([−0.044,0.063]), and Δg1 Z ([−0.0087,0.024]). These limits are also translated into their effective field theory equivalents: cWWW/Λ2 ([−2.7,2.7] TeV−2), cB/Λ2 ([−14,17] TeV−2), and cW/Λ2 ([−2.0,5.7] TeV−2).